Detection rate of blood group alloimmunization based on real‐world testing practices and kinetics of antibody induction and evanescence. Issue 11 (9th July 2016) - Stack, Gary; Tormey, Christopher A.
Abstract : BACKGROUND: Failure to detect non‐ABO blood group alloantibodies places patients at risk for hemolytic reactions. Suboptimal alloantibody detection could result from posttransfusion testing performed too early, too late, or not at all. Testing performed too early may precede antibody induction, while testing performed too late could miss antibodies that have evanesced. Taking these factors into account, our goal was to determine the percentage of alloantibodies detected with real‐world testing practices. STUDY DESIGN AND METHODS: The alloantibody detection rate in a general hospital setting was determined based on the frequency and timing of antibody testing after red blood cell (RBC) transfusions and rates of antibody induction and evanescence. Intervals to follow up testing after RBC transfusions (n = 561 RBC units in 100 random patients) were determined retrospectively. Best‐fit lines and equations for antibody induction and evanescence were computed on previously published data. RESULTS: Nearly half (271/561; 48.3%) of RBC infusions had either no follow‐up antibody screen or testing too soon (<30 days) after transfusion to detect alloimmunization. Of the remaining RBC units, 10.3% (58/561) had follow‐up testing 30 to 112 days posttransfusion, 28.7% (161/561) were followed up at more than 112 days, and 12.7% (71/561) were tested at both 30 to 112 days and more than 112 days. By inputting these timing data into best‐fit line equations for antibody induction and evanescence, we calculated an alloantibody detection rate of 31.6%. CONCLUSION: Posttransfusion antibody testing was inadequately timed for optimal alloantibody detection. Real‐world compatibility testing was predicted to detect less than one‐third of non‐ABO antibodies, thereby exposing patients to risks of mismatched transfusion.